2013
DOI: 10.1063/1.4812015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of avalanche precursors by acoustic probing in the bulk of tilted granular layers

Abstract: International audienceUnderstanding the precursors of granular avalanches is important for the prediction of critical events. As part of the dynamics leading to the avalanche, precursors are identified as collective motions of grains on the free surface. When a granular pile is tilted at a constant angular velocity, precursors appear quasi-periodically. In this paper we simultaneously caracterize precursors on the free surface with an optical method and in the bulk with acoustic methods (nonlinear and linear).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…In this case, strong correlations between surface and bulk rearrangements can be revealed (Fig. 3) [27,28]. They show strong variations of the weak contact network during the tilt especially just before avalanche triggering (Fig.…”
Section: Nonlinear Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, strong correlations between surface and bulk rearrangements can be revealed (Fig. 3) [27,28]. They show strong variations of the weak contact network during the tilt especially just before avalanche triggering (Fig.…”
Section: Nonlinear Methodsmentioning
confidence: 99%
“…In this case, strong correlations between surface and bulk rearrangements can be revealed (Fig. 3) [27,28]. The surface rearrangements (Fig.…”
Section: Nonlinear Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duranteau el al. [20] have demonstrated the strong correlations between optical and acoustical detections of precursors. They have shown that precursors are both of geometrical nature (at least at the surface) and of elastic nature in the bulk of the layer (at least down to a certain depth).…”
Section: A Context Of Dry Avalanchesmentioning
confidence: 99%
“…But all these first experiments [14,16,24,35] and more recent studies [20,25,36,37] dedicated to the identification of the precursors have been essentially performed in a dry atmosphere, with a relative humidity up to about 50 %.…”
Section: A Context Of Dry Avalanchesmentioning
confidence: 99%